2009
DOI: 10.2458/v16i1.21689
|View full text |Cite
|
Sign up to set email alerts
|

"It just goes to kill Ticos": national market regulation and the political ecology of farmers' pesticide use in Costa Rica

Abstract: This paper addresses pesticide residues on vegetables in developing countries through the specific case of Costa Rica.  Pesticide residues are often very high on vegetables in developing countries, generally considerably higher than in industrialized countries.  Using a political ecology approach, I combine qualitative and quantitative primary data with secondary data to answer two questions.  Why do farmers use pesticides in a manner that results in high levels of residues on vegetables?  And, how do markets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 82 publications
0
26
0
1
Order By: Relevance
“…Galt (2009) for sediment capture and cover cropping have been shown to reduce weed pressure, minimize erosion and increase yields without chemical inputs in Latin America (M. A. Altieri 1999) and China and Kenya (Uphoff 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galt (2009) for sediment capture and cover cropping have been shown to reduce weed pressure, minimize erosion and increase yields without chemical inputs in Latin America (M. A. Altieri 1999) and China and Kenya (Uphoff 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We found that economic considerations weighed heavily in food crop management decisions. Economic constraints often determined how, when, and which chemicals were applied (Galt 2009). However, farmers did not keep written records of their farm expenses so they were not aware of their costs and crop value until participating in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, I made a choice to present the data in a way that highlighted the most substantial variation, which was across different market types, as a result of uneven regulation in the commodity chain that I theorize and show empirically. Mutersbaugh's question, however, gives me the opportunity to note that the relationship between farm scale and pesticide use is complex, as I have presented elsewhere (Galt 2008). In this other analysis, I showed that among minisquash export farmers and national market potato farmers, farmers personally spraying pesticides (rather than having a hired crew do it) was strongly and negatively related to pesticide use intensity.…”
Section: Review By Tad Mutersbaugh Department Of Geography Universimentioning
confidence: 91%
“…I would add the importance of engaging national market producers in a similar effort, which could be spurred by better national market regulations. Elsewhere I have examined farmer subjectivities as they relate to pesticides (Galt 2013a), and in the conclusion of that piece I call for a similar approach to what Reynolds has suggested. This would be very time-intensive work that would be perfectly suited for a PhD student looking for a challenging and rewarding project and who has a lifestyle allowing for long periods of field work.…”
Section: Review By Tad Mutersbaugh Department Of Geography Universimentioning
confidence: 99%
“…Mutersbaugh's question, however, gives me the opportunity to note that the relationship between farm scale and pesticide use is complex, as I have presented elsewhere (Galt 2008). Mutersbaugh is correct that in the chapter focusing on export farmers (Chapter 5) I discuss them as a whole.…”
Section: Review By Tad Mutersbaugh Department Of Geography Universimentioning
confidence: 99%